Cosmology with the Roman Space Telescope – multiprobe strategies. Issue 2 (1st July 2021) - Eifler, Tim; Miyatake, Hironao; Krause, Elisabeth; Heinrich, Chen; Miranda, Vivian; Hirata, Christopher; Xu, Jiachuan; Hemmati, Shoubaneh; Simet, Melanie; Capak, Peter; Choi, Ami; Doré, Olivier; et al.
ABSTRACT: We simulate the scientific performance of the Nancy Grace Roman Space Telescope High Latitude Survey (HLS) on dark energy and modified gravity. The 1.6-yr HLS Reference survey is currently envisioned to image 2000 deg 2 in multiple bands to a depth of ∼26.5 in Y, J, H and to cover the same area with slit-less spectroscopy beyond z = 3. The combination of deep, multiband photometry and deep spectroscopy will allow scientists to measure the growth and geometry of the Universe through a variety of cosmological probes (e.g. weak lensing, galaxy clusters, galaxy clustering, BAO, Type Ia supernova) and, equally, it will allow an exquisite control of observational and astrophysical systematic effects. In this paper, we explore multiprobe strategies that can be implemented, given the telescope's instrument capabilities. We model cosmological probes individually and jointly and account for correlated systematics and statistical uncertainties due to the higher order moments of the density field. We explore different levels of observational systematics for the HLS survey (photo -z and shear calibration) and ultimately run a joint likelihood analysis in N- dim parameter space. We find that the HLS reference survey alone can achieve a standard dark energy FoM of >300 when including all probes. This assumes no information from external data sets, we assume a flat universe however, and includes realistic assumptions for systematics. Our study of the HLS reference survey should be seen as part of a future community-driven effort to simulate and optimize the science return of the Roman Space Telescope .